Transcriptome Modifications in Porcine Adipocytes via Toll-Like Receptors Activation - Igata, Manami; Islam, Md. Aminul; Tada, Asuka; Takagi, Michihiro; Kober, A. K. M. Humayun; Albarracin, Leonardo; Aso, Hisashi; Ikeda-Ohtsubo, Wakako; Miyazawa, Kenji; Yoda, Kazutoyo; He, Fang; Takahashi, Hideki; et al. (Frontiers in Immunology, 2019)
Adipocytes are the most important cell type in adipose tissue playing key roles in immunometabolism. We previously reported that nine members of the Toll-like receptor (TLR) family are expressed in an originally established porcine intramuscular adipocyte cell line. However, the ability of TLR ligands to modulate immunometabolic transcriptome modifications in porcine adipocytes has not been elucidated. Herein, we characterized the global transcriptome modifications in porcine mature adipocytes (PMA) following stimulation with Pam3csk4, Poly(I:C) or LPS which are ligands for TLR2, TLR3 and TLR4, respectively. Analysis of microarray data identified 530 (218 up, 312 down), 520 (245 up, 275 down) and 525 (239 up, 286 down) differentially expressed genes (DEGs) in PMA following the stimulation with Pam3csk4, Poly(I:C) and LPS, respectively. Gene ontology classification revealed that DEGs are involved in several biological processes including those belonging to immune response and lipid metabolism pathways. Functionally annotated genes were organized into two groups for downstream analysis: immune response related genes (cytokines, chemokines, complement factors, adhesion molecules and signal transduction), and genes involved with metabolic and endocrine functions (hormones and receptors, growth factors and lipid biosynthesis). We inferred protein interaction networks from common DEGs and found that EGR1, NOTCH, NOS2, TNFAIP3, TRAF3IP1, INSR, CXCR4, PPARA, MAPK10 and C3 are the major hub genes of TLR induced transcriptional network of porcine adipocyte. Potential hubs of protein interaction network also exhibited higher centrality estimates in the Gene-Transcription factor interaction network. Our results provide new insights of transcriptome modifications associated with TLRs activation in porcine adipocytes and identified key regulatory genes that could be used as biomarkers for the evaluation of immune-modulators having functional beneficial effects in porcine adipocytes.